2023
DOI: 10.3389/fendo.2023.1087437
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of poor glycemic control among type 2 diabetes mellitus patients at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia: Unmatched case-control study

Abstract: BackgroundPoor glycemic control is one of the most determinant factors for type 2 diabetes-related morbidity and mortality. The proportion of type 2 diabetes mellitus patients with poor glycemic control remains high. Yet evidence on factors contributing to poor glycemic control remains scarce. The aim of this study is to identify determinants of poor glycemic control among type 2 diabetes mellitus patients at a diabetes mellitus clinic in University of Gondar Comprehensive Specialized Hospital, Northwest Ethio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
(76 reference statements)
1
3
1
2
Order By: Relevance
“…Similarly, the study outcome of Cheneke, et al 67 found that even though the study participants were on diabetes treatment, the majority of them were found to have poor glycemic control. Similar studies in the sub-Saharan Africa context by Govender, et al, 68 and Legese, et al, 69 have shown that poor fasting blood glucose and haemoglobin A1C status have been found among diabetic patients. Again, we found that 40.8% of the study participants in our research recorded high total cholesterol levels with a little below half recording high triglyceride levels above 1.71mmol/L.…”
Section: Discussionsupporting
confidence: 65%
“…Similarly, the study outcome of Cheneke, et al 67 found that even though the study participants were on diabetes treatment, the majority of them were found to have poor glycemic control. Similar studies in the sub-Saharan Africa context by Govender, et al, 68 and Legese, et al, 69 have shown that poor fasting blood glucose and haemoglobin A1C status have been found among diabetic patients. Again, we found that 40.8% of the study participants in our research recorded high total cholesterol levels with a little below half recording high triglyceride levels above 1.71mmol/L.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, our study observed poor glucose control in patients with poor dietary adherence, physical activity adherence, and medication adherence, a finding also observed in Bangladesh (Afroz et al, 2019) and Ethiopia (Legese et al, 2023). The Ethiopian study was a hospitalbased cross-sectional study involving 180 adults living with type 2 diabetes attending a diabetic clinic in Gondar town near Addis Abba, as opposed to our study which was community-based.…”
Section: Discussioncontrasting
confidence: 41%
“…Additionally, lifestyle factors, including excess alcohol intake, smoking, physical inactivity, unhealthy diet, and educational level (Dubale et al, 2023;Chetoui et al, 2019;Bitew et al, 2023;Demoz et al, 2019;Legese et al, 2023), are predictive of a patient's blood glucose level. For example, a study by Abdullah et al (2019), aimed to determine predictors of good glycemic control among patients with type 2 diabetes in rural Malaysia, found that shorter diabetes duration was a predictor of good glycemic control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was calculated by considering the following assumptions for unmatched case control study in Epi info version 7.2.6.0 software using the following assumptions: 95% Con dence level (probability of committing α error) to be 1.96 ,90% power (probability of rejecting a true difference), control to case ratio of 2:1, and proportion of main exposure variable (persistent proteinuria among controls to be 14.4% with its adjusted odds ratio of 3.96 from previous studies (29) yielding the largest sample size of 153 ( 102 controls and 51 cases ). However, we included two additional controls and one case at spot during data collection and analyzed data from 156(104 controls and 52 cases ).Although, we considered the exposure variables such as adherence to diabetes diet and medication, physical exercise and comorbidities to estimate the sample size, they yielded less sample size for this study.…”
Section: Sampling Size Determinationmentioning
confidence: 99%